ENHANCING COMPETITIVENESS OF PERUVIAN TEXTILE MSES THROUGH QUALITY MANAGEMENT: A FOCUS ON LEADERSHIP, TRAINING, AND CONTINUOUS IMPROVEMENT - Munive, Marco Antonio Ledesma (LPPM Universitas Jambi, 2024)
This study examines the impact of quality management on the competitiveness of micro and small enterprises (MSEs) in the Peruvian textile clusters, a sector that is a significant driver of local economic activity. Unlike previous studies, this research provides a comprehensive analysis of the combined influence of leadership, employee training, customer orientation, continuous improvement, and benchmarking on MSE competitiveness. Utilizing a robust quantitative research design, data were collected from 347 participants through a structured survey. The findings reveal a high level of engagement in quality management practices among the surveyed MSEs, with the identified factors significantly contributing to improved productivity, customer satisfaction, and market presence. The originality of this study lies in its in-depth exploration of these quality management dimensions within the specific context of Peruvian textile clusters, offering new insights into their role in driving competitiveness. The implications are particularly relevant for business owners, managers, and policymakers seeking to enhance the sustainability and competitive advantage of textile MSEs in a highly dynamic market environment.